ANALISIS PENGARUH CUSTOMER RELATIONSHIP MARKETING TERHADAP NILAI NASABAH DAN KEUNGGULAN PRODUK DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS NASABAH (Studi pada PT Bank BRI Kantor Cabang Batang) - Haryunanto, Antonius Bertiyudho; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2014)
This study aimed to examine the effect of customer relationship marketing , customer value and product excellence to customer satisfaction and its impact on the improvement of customer loyalty . The use of these variables with the results of previous studies of reasons , namely : Tax , Brown and Chandrasekaran (1998 ) , Mital , Ross and Baldasare (1998 ) , Too , Souchon , and Thirkell ( 2000) and Leo YM Sin et al ( 2002) who found direct influence of customer relationship marketing , customer value and product excellence to customer satisfaction and its influence on customer loyalty . The use of these variables can solve problems that occur in the PT. Trunk BRI branches , namely the high level of criticism received by PT . Trunk BRI branch offices that have an impact on customer loyalty is low . The sample was customers of PT . BRI branch offices of Batang, some 100 people. used SPSS 16.00 to analyze the data , analysis results show that customer relationship marketing is positive and significant impact on customer value and product excellence, customer value and product excellence and significant positive effect on customer satisfaction, customer satisfaction and a significant positive effect on customer loyalty . The empirical findings indicate that in order to increase customer loyalty, which is the cause of the high level of criticism received by PT .BRI branch offices of Batang need to consider factors such as customer relationship marketing , customer value , customer satisfaction and product excellence , because these factors shown to affect the level of customer loyalty . Theoretical implications and suggestions for future research are also outlined at the end of this research. Keywords: customer relationship marketing, customer value, product advantage, customer satisfaction, customer loyalty